2009
DOI: 10.1103/physreva.79.062703
|View full text |Cite
|
Sign up to set email alerts
|

Absolute elastic differential cross sections for electron scattering byC6H5CH3andC

Abstract: We present absolute differential cross sections ͑DCS͒ for elastic scattering from two benzene derivatives C 6 H 5 CH 3 and C 6 H 5 CF 3 . The crossed-beam method was used in conjunction with the relative flow technique using helium as the reference gas to obtain absolute values. Measurements were carried out for scattering angles 15°-130°and impact energies 1.5-200 eV. DCS results for these two molecules were compared to those of C 6 H 6 from our previous study. We found that ͑1͒ these three molecules have DCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 18 publications
4
30
0
Order By: Relevance
“…3-6, we compare the present DCS measurements at 10, 15, 20, and 30 eV, respectively, with our IAM-SCAR and R-matrix results. There are no previous DCS 1,4-dioxane measurements that we are aware of, however, corresponding results for scattering from benzene 25,26 and pyrazine 24 are included throughout Figs. 3-6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3-6, we compare the present DCS measurements at 10, 15, 20, and 30 eV, respectively, with our IAM-SCAR and R-matrix results. There are no previous DCS 1,4-dioxane measurements that we are aware of, however, corresponding results for scattering from benzene 25,26 and pyrazine 24 are included throughout Figs. 3-6.…”
Section: Resultsmentioning
confidence: 99%
“…It is thus interesting, and possibly quite instructive, to compare the scattering cross sections for these three molecules to see if any trends emerge and whether or not those trends can be associated with their intrinsic physico-chemical properties. Such a comparison is only now possible due to recent detailed studies on pyrazine, 23,24 earlier work on benzene 25,26 and the current measurements with 1,4-dioxane. Note that this systematic comparison of the scattering behaviour for benzene, pyrazine, and 1,4-dioxane (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This result is not unexpected, since similar behaviour was found in earlier studies 50 with benzene and pyrimidine. The experimental elastic angular distributions of these targets 36,51 are also characterized by the presence of a shoulder around 40 • , which our IAM-SCAR theory fails to predict. In addition, for energies below 100 eV, the benzene and pyrimidine IAM-SCAR cross sections always lie above the measurements in the angular range 10 • -50 • , such as we observe here for pyrazine.…”
Section: B Differential Cross Sectionsmentioning
confidence: 94%
“…Moreover, for energies above 100 eV, the lower energy discrepancies in benzene and pyrimidine disappear, and an excellent agreement was found in the entire angular range. 36,48,51 Unfortunately, for pyrazine, there are no further experimental data available in the literature for electron collisions at energies higher than 50 eV. Given the similarities among the three molecules, both in structure and physico-chemical properties, it is reasonable to expect the pyrazine IAM-SCAR results to be accurate for θ > 50 • in the energy range 50-100 eV, and in the entire angular range for energies above 100 eV ( Fig.…”
Section: B Differential Cross Sectionsmentioning
confidence: 99%
“…In our research program at Sophia University for such series of molecules, we have reported absolute differential cross sections (DCSs) for elastic electron scattering from CH n F 4-n (n = 0-4), 1, 2 XY 4 (X = C, Si, Ge; Y = H, F, Cl), [3][4][5][6] CX 3 Y (X = H, F; Y = H, F, Cl, Br, I), 7,8 C 3 H 8 and C 3 F 8 , 9 C 6 H 5 X (X = CH 3 , CF 3 ), 10 and CO 2 , OCS, and CS 2 . 11, 12 Those results have been compared with the corresponding elastic cross sections in Ne, Ar, Kr, and Xe (see, e.g., Ref.…”
Section: Introductionmentioning
confidence: 99%